Falta de normatividad en el código de la niñez y la adolescencia que hagan efectivo el reembolso de los gastos sufragados por el demandado cuando el resultado de la prueba de ADN descarta su paternidad. - Tuarez Gaibor, Blanca Gremilda (2014)
In modern societies, children and adolescents deserve special attention in recognition to the principle of best interests of their disadvantaged status in hostile social media as seen today. However, the higher score in any way imply ignoring the interests of other components, as the child's needs must be balanced against the needs of all people within a logic of integration. The question is the primacy of the rights of children in its confrontation with other rights that might impair or detract from, or in respect of rules or provisions that may result from such a situation. This is imposed on the ordinary courts the obligation to apply the principle of best interests, trying to determine clearly the extent of the rights of children and adolescents, priority, and the limits they have in case of conflict with rights others, and the legal means for providing adequate protection. In this sense, the laws that should guarantee the balance between the principle that the interests of the child or adolescent, and the rights of others, however, the Code of Children and Adolescents suffering from empty violate such rights as the right to reimbursement of expenses incurred by demand for food, when the result of DNA tests rule out fatherhood. This loophole undermines the principles of contradiction and right to defense, as in the legal body described above there are no legal mechanisms, preemptive rights of children and adolescents, but without undermining the rights of the defendant for food, who would attend their right to reimbursement of expenses incurred by the practice of DNA testing, when they dismiss the paternity. It should also indicate that food processors are the most common and frequent in the administration of justice throughout the country, so this social problem deserves urgent solution.